1988
DOI: 10.1002/hup.470030107
|View full text |Cite
|
Sign up to set email alerts
|

The effect of clonidine and bright light on plasma melatonin

Abstract: We studied the effect of the az-adrenoceptor agonist, clonidine, and bright artificial light (>2500 lux) on the nocturnal increase in plasma melatonin in normal subjects. Clonidine (1.5 pg/ kg, intravenously) was without effect on plasma melatonin concentration. In contrast, bright light treatment abolished the increase in night-time melatonin. Bright light is a simple and effective means of altering melatonin secretion in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Lewy et al [1986] reported a dose-dependent reduction in plasma melatonin concentration following clonidine administration to normal subjects. Grasby and Cowen [1988] using a smaller dose of clonidine, failed to replicate this finding, suggesting that changes in melatonin secretion may be strongly dependent on the a 2 -agonist dose. Anyway, changes in diurnal melatonin levels induced by clonidine are difficult to detect due to the low levels of the hormone during the morning and its normal circadian decay.…”
Section: Discussionmentioning
confidence: 96%
“…Lewy et al [1986] reported a dose-dependent reduction in plasma melatonin concentration following clonidine administration to normal subjects. Grasby and Cowen [1988] using a smaller dose of clonidine, failed to replicate this finding, suggesting that changes in melatonin secretion may be strongly dependent on the a 2 -agonist dose. Anyway, changes in diurnal melatonin levels induced by clonidine are difficult to detect due to the low levels of the hormone during the morning and its normal circadian decay.…”
Section: Discussionmentioning
confidence: 96%